RELEVANSI STRATEGI DAKWAH HIZBUT TAHRIR INDONESIA DENGAN STRATEGI DAKWAH NABI MUHAMMAD SAW - Eunis Khoerunnisa (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2015)
Hizbut Tahrir Indonesia is a unique and phenomenal propaganda institution. For one decade (1998-2008) it has exercised a very intensive preaching, conception of Islam, enforcement of Syari’ah and the Khilafah ruling system. The purpose of this study is to determine the Hizbut Tahrir Indonesia thinking about: (1) the arguments used by Hizbut Tahrir Indonesia in preaching; (2) the purpose of the preaching of Hizbut Tahrir Indonesia; (3) the method used in the propaganda activities of Hizbut Tahrir Indonesia; (4) the program of propaganda in the view of Hizbut Tahrir Indonesia; and (5) the relevance of Hizbut Tahrir Indonesia propagation strategy with the strategy of propaganda of the Prophet Muhammad. The results showed that (1) Hizbut Tahrir Indonesia propagation argument is Surah (Chapter) Ali-Imran verse 104; (2) the purpose of Hizbut Tahrir Indonesia propaganda is to hold Islamic life and to carry the Islamic propagation to the entire world and to revive Islam in the right way; (3) the method adopted by Hizbut Tahrir Indonesia in carrying out the mission is the laws of Personality which is taken from Prophet Sayings; (4) HizbutTahrir Indonesia propagation program is basically the same as Hizbut Tahrir anywhere, for espousing ideas, ideals and the same activity which reflects on propagation strategy of the Prophet; and (5) selection of Hizbut Tahrir Indonesia toward the Prophet Traditions about the propagation method applied by the Prophet Muhammad SAW tend to choose a more nuanced firm. In fact, the propagation method applied by the Prophet varies depending on the existing situation and conditions. Hizbut Tahrir Indonesia adalah sebuah lembaga dakwah yang unik dan fenomenal. Selama kurang lebih satu dasawarsa (1998-2008) sangat intensif melakukan dakwahnya, konsepsinya tentang penegakan Syari’at Islam dan sistem pemerintahan Khilafah. Tujuan penelitian ini adalah untuk mengetahui pemikiran Hizbut Tahrir Indonesia tentang: (1) landasan yang digunakan  oleh Hizbut Tahrir Indonesia dalam berdakwah; (2) tujuan dakwah Hizbut Tahrir Indonesia; (3) metode yang digunakan dalam kegiatan dakwah Hizbut Tahrir Indonesia; (4) program dakwah menurut pandangan Hizbut Tahrir Indonesia; dan (5) relevansi strategi dakwah Hizbut Tahrir Indonesia dengan strategi dakwah Nabi Muhammad SAW. Hasil penelitian menunjukkan bahwa (1) landasan dakwah Hizbut Tahrir Indonesia adalah QS. Ali-Imran ayat 104; (2) tujuan dakwah Hizbut Tahrir Indonesia adalah melangsungkan kehidupan Islam dan mengemban dakwah Islam ke seluruh penjuru dunia dan untuk membangkitkan kembali umat Islam dengan cara yang benar; (3) metode yang ditempuh oleh Hizbut Tahrir Indonesia dalam melaksanakan dakwah adalah hukum-hukum syara’ yang diambil dari thariqah Rasulullah SAW; (4) program dakwah Hizbut Tahrir Indonesia pada dasarnya sama dengan Hizbut Tahrir di manapun, karena mengemban pemikiran, cita-cita dan aktivitas yang sama, yaitu bercermin pada metode dakwah Rasulullah SAW; dan (5) Pemilihan Hizbut Tahrir Indonesia terhadap Hadits-hadits tentang metode dakwah yang diterapkan oleh Nabi Muhamad SAW cenderung memilih Hadits-hadits yang bernuansa lebih tegas. Padahal, metode dakwah yang diterapkan oleh Nabi sangat bervariasi bergantung kepada situasi dan kondisi yang ada.